Analisis Pelaksanaan Prosedur Audit atas Persediaan dalam Upaya Menilai Kewajaran Laporan Keuangan Klien (Studi pada KAP X) - Aulia Puteri Sonjaya; Ela Anggraeni; Sintauli Sitorus; Azka Aulia; Eka Merdekawati (CV. ITTC INDONESIA, 2025)
This study aims to evaluate the implementation of audit procedures on inventory accounts at KAP X and assess their compliance with the relevant Auditing Standards (SA), particularly SA 315, SA 330, and SA 501. Inventory is an account with a high risk of misstatement, requiring adequate audit procedures to ensure its existence, valuation, and completeness. The study employs a qualitative case study approach through interviews, observations, and review of audit documentation. The results indicate that most of the audit procedures performed by KAP X are in accordance with the Standards, especially in terms of physical inventory inspection, reconciliation of inventory records, evaluation of valuation methods, and assessment of the client’s internal controls. However, several challenges were identified, such as limited supporting documents for inventory movements, suboptimal timing of stock-taking, and audit documentation that has not fully complied with SA 230. Overall, the audit procedures are considered adequate to provide reasonable assurance regarding the fairness of the inventory balance, although improvements are still needed in the areas of audit evidence and documentation consistency.